Development and validation of a new Prescription Quality Index - Hassan, Norul Badriah (Blackwell Science Inc, 2010)
AIMS: The aims were to develop and validate a new Prescription Quality Index (PQI) for the measurement of prescription quality in chronic diseases. METHODS: The PQI were developed and validated based on three separate surveys and one pilot study. Criteria were developed based on literature search, discussions and brainstorming sessions. Validity of the criteria was examined using modified Delphi method. Pre-testing was performed on 30 patients suffering from chronic diseases. The modified version was then subjected to reviews by pharmacists and clinicians in two separate surveys. The rater-based PQI with 22 criteria was then piloted in 120 patients with chronic illnesses. Results were analysed using SPSS version 12.0.1 RESULTS: Exploratory principal components analysis revealed multiple factors contributing to prescription quality. Cronbach's α for the entire 22 criteria was 0.60. The average intra-rater and inter-rater reliability showed good to moderate stability (intraclass correlation coefficient 0.76 and 0.52, respectively). The PQI was significantly and negatively correlated with age (correlation coefficient −0.34, P < 0.001), number of drugs in prescriptions (correlation coefficient −0.51, P < 0.001) and number of chronic diseases/conditions (correlation coefficient −0.35, P < 0.001). CONCLUSIONS: The PQI is a promising new instrument for measuring prescription quality. It has been shown that the PQI is a valid, reliable and responsive tool to measure quality of prescription in chronic diseases.